Determinants of Time for Publication Annual Reports: Empirical Evidence from Non-Financial Listed Companies in Vietnam - Anh Huu Nguyen; Hieu Thanh Nguyen; Chung Quang Tran; Lien Quynh Le (International Journal of Financial Studies, 2022)
This article studied the factors affecting the time taken for annual report submission through an analysis of 654 non-financial listed companies on the Vietnamese stock market from 2016 to 2020. Data collected were processed by using fixed-effect models (FEM), random effect models (REM), adjusted REM, and general least square (GLS) to ensure the validity of research results. The main objective of this paper was to explore the effects of independent variables including retained earnings (RETA), earnings before interest and tax (EBITTA), liquidity (WCTA), capital structure (BVETD), bankruptcy risk (ZSCORE), size (SIZE), number of years in business (AGE), characteristics of financial reports (CONSO), and type of audit firm (AUDIT) on the number of days for publication annual reports (TIME). The results obtained from the adjusted-REM and GLS regression showed that retained earnings, firm age, and firm size have positive effects on time for disclosure annual reports, whereas earnings before interest and tax and audit firm type have negative effects. In addition, the results showed that working capital, capital structure, feature of consolidated reports, and bankruptcy risk have no significant effects on time to publish annual reports.